Tracking the Footprints of the Veda Teachings Implementation Study on Hindus in Bali - Pastika, Mangku; Ngurah Sudiana, I Gusti; Purnamawati, Sri Putri; D.E, Relin (International Journal of Engineering, Science and Information Technology, 2025)
The Vedic teachings have been the primary foundation of the religious and social life of the Balinese Hindu community. As part of the spiritual heritage of ancient India, these teachings entered Bali through trade routes and cultural migration since the first century AD. Over time, the Vedic teachings have been acculturated with local culture, creating unique and dynamic Balinese Hindu practices. This study examines how the Vedic teachings in Bali are applied in everyday life, social systems, and religious practices, focusing on the concepts of dharma, karma, and moksha, which remain the ethical guidelines of the community. The research method used is qualitative with a descriptive narrative approach, involving interviews with religious figures, direct observation of yadnya rituals, and analysis of historical and religious documents. Through this approach, the study seeks to understand how the Balinese Hindu community internalizes the Vedic teachings in their lives, individually and collectively. Oral traditions and religious rituals are the primary means of preserving the Vedic teachings, which are adapted to the local social and cultural context. The results of the study show that although the Vedic teachings remain the basis of the spiritual life of the Balinese Hindu community, the process of adaptation and acculturation has formed religious practices different from the Vedic teachings that developed in India. Balinese society maintains core values such as dharma and karma. It aligns them with local concepts such as desa, kala, and patra, which allow flexibility in implementing rituals and religious rules. The role of brahmanas as guardians of the Vedic teachings is still vital in the social structure, but changing times bring new challenges to the sustainability of these teachings, especially in the face of modernization and globalization. Modernization and urbanization have given rise to various shifts in religious practices, sometimes leading to the reduction of spiritual meaning and the transformation of rituals into mere formalities. Hindu religious education in Bali can play a role in strengthening the community's understanding and appreciation of the Vedic teachings with methods that are more contextual and relevant to the times. Overall, the Vedic teachings still play a central role in the lives of Balinese Hindu society, although in a form that has undergone modification and acculturation. Academic studies and cultural preservation are strategic steps in maintaining the sustainability of this spiritual heritage amidst changing times. This study emphasizes the importance of preservation efforts through an empirical approach that explores the actual practice of the Vedic teachings and pays attention to how the Balinese Hindu community maintains its religious identity amid globalization.